United Nations Commission on International Trade Law (UNCITRAL) Yearbook 2010 - United Nations (United Nations, 2014)
The Yearbook of the United Nations Commission on International Trade Law reproduces the substantive documents prepared each year for the Commission and its working groups. It also includes the annual report of the Commission, meeting records, General Assembly resolutions and Sixth Committee reports related to UNCITRAL’s work, and a bibliography of recent scholarly writings examining the legal texts prepared by UNCITRAL. The Yearbook is divided into three parts. Part One deals with the Commission’s report. Part Two covers studies and reports on specific subjects. Part Three contains meeting records, the bibliography and checklists of UNCITRAL documents prepared in the current and previous years.